HAEMODYNAMIC PRESERVATION IN CESAREAN SECTIONS BY LOW DOSE 0.5% HYPERBARIC BUPIVACAINE - Ahmad, Maqsood; Ahmad, Mumtaz; Atif, Naveel (Journal of Ayub Medical College Abbottabad, 2017)
Background: Spinal anaesthesia is technique of choice for caesarean sections and hyperbaric bupivacaine is a recommended drug for this popular block. Although safe but few complications are haemodynamic changes, postdural puncture headache, cauda equina syndrome and radiculopathy. However, hypotension remains the common side effect which is believed to occur in 95% of patients resulting in reduction of uteroplacental perfusion causing foetal acid-base abnormalities. Various doses regimes are in safe anaesthesia practice for providing regional anaesthesia for such patients with least detrimental effects on foetal outcome. This study was carried out to find the effective dose of 0.5 % hyperbaric bupivacaine in caesarean section patients by comparing two different doses. Methods: After enrolling two hundred patients of C section (Caesarean section) for this study, 90 patients were selected to compare the effects of 0.5% hyperbaric bupivacaine. Group A (n=45) received 10 mg of drug while group B (n=45) received 12 mg for spinal anaesthesia. Onset of block, sensory and motor level, haemodynamic changes, surgery time, maternal satisfaction, APGAR score and incidence of complications were compared in two groups. Results: Blood pressure decreases were less in Group A (p-0.074) but not statistically significant. Phenylephrine for hypotension was given to 17% vs 5% in group B. Maternal satisfaction was found to be better in group B 33 vs 17 but was statistically significant (p 0.034). 2% patients had bradycardia in group A which was treated by atropine. No complications were reported in either group. Conclusion: Doses of hyperbaric bupivacaine for spinal anaesthesia in caesarean sections must be at least 12 mg because it produces excellent anaesthesia and maternal satisfaction without complications. Keywords: hyperbaric bupivacaine 0.5 %; spinal anaesthesia; C-section; Bupivacaine; Haemodynamic